Pengetahuan Tentang Karies Gigi Pada Siswa Kelas VII SMP Negeri 28 Surabaya Tahun 2023 - Amelia Ayu Widya Ardhana; Imam Sarwo Edi; Ratih Larasati (SURABAYA DENTAL THERAPIST JOURNAL, 2023)
Introduction: Dental caries is a chronic disease, a fairly long-term process caused by bacteria in the form of a continuous loss of mineral ions from the crown or root enamel surface of the tooth. According to 2018 Basic Health Study Results (RISKESDAS) data, the prevalence of dental and oral health problems nationwide is 57.6% of the Indonesian population. The porosity of East Java is 42.4%. According to WHO, 34.32% of 12-year-olds have tooth decay. Dental caries develops in school-aged children due to several factors. One of them is knowledge about tooth decay in children. Problem: A problem with this study was the high average caries rate among students in class VII of SMP Negeri 28 Surabaya. The purpose: The purpose of this study is to check the knowledge of dental caries among students in Class VII of SMP Negeri 28 Surabaya. Method: This type of research is descriptive research. The subjects of this study were 34 of her 12-year-old students in grades VII-E and VII-F who completed a questionnaire. A data analysis technique that calculates the average of each response based on the respondent's score and displays the percentages in a tabular format. Result: The results of this study are 7th grade caries from SMP Negeri 28 Surabaya belonging to the moderate category.